University of South Africa staff’s learning experiences in online coursework master’s of education - Gumbo, M.T.; Minnaar, A. (South African Journal of Higher Education, 2019)
This study explored the experiences of University of South Africa (UNISA) staff who did an Open and Distance Learning (ODL) based Master’s of Education (MEd) programme between the years 2012 and 2015. This is an online programme that was initiated jointly by UNISA and University of Maryland University College (UMUC). Only academics who UNISA employs were targeted in this study due to UNISA’s rationale for engaging in this dual university initiative. A cohort of these academics had already qualified with doctoral and professional master’s degrees in various focus areas. We were interested in these academics’ varied experiences with respect to their views, understandings and needs in this online programme. What are the staff’s experiences of learning online in the UNISA-UMUC MEd programme? This question triggered research into the experiences of the academics concerned. This qualitative phenomenographic study was framed in the variation theory. Seven purposively selected staff members were interviewed using semi-structured interview guide. Three main themes emerged from the data namely, experiences of staff pertaining to learning online, subject matter and student learning, and the learning tools related to social media. The study’s findings revealed that participants varied in their experiences of online learning in the dual university initiative. The findings were important for this dual university initiative in so far as improvements that may be necessitated by the findings are concerned.